2018
DOI: 10.1101/328419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reciprocal Modulation Between Amyloid Precursor Protein and Synaptic Membrane Cholesterol Revealed By Live Cell Imaging

Abstract: 2 Summary (150 words)The amyloid precursor protein (APP) has been extensively studied because of its relevance to Alzheimer's disease (AD). However, its membrane distribution and neuronal function remains unclear. Here, we generated an APP fusion protein with a pH-sensitive green fluorescent protein at its ectodomain and a pH-insensitive blue fluorescent protein at its cytosolic domain to measure surface and intracellular APP distributions and its cleavage events. This fusion protein, closely resembling endoge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 102 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…However, this may be an interesting hypothetical perspective and should be checked further by functional studies. Similar ideas have been suggested as the reciprocal modulations between Aβ production and cholesterol homeostasis in the cellular trafficking of cholesterol [ 49 , 50 ] and between APP and synaptic membrane cholesterol [ 51 ]. However, cholesterol biosynthesis was not central to their suggestions.…”
Section: Discussionmentioning
confidence: 58%
“…However, this may be an interesting hypothetical perspective and should be checked further by functional studies. Similar ideas have been suggested as the reciprocal modulations between Aβ production and cholesterol homeostasis in the cellular trafficking of cholesterol [ 49 , 50 ] and between APP and synaptic membrane cholesterol [ 51 ]. However, cholesterol biosynthesis was not central to their suggestions.…”
Section: Discussionmentioning
confidence: 58%
“…In summary, we propose a potential mechanism to explain the fundamental role of cholesterol in AD, underscored by the multiple genetic studies that have identified polymorphisms in genes related to cholesterol metabolism and the incidence of AD (Dong et al, 2017), including, most prominently, APOE. Moreover, our data help clarify the interdependence between cholesterol and APP metabolism (Marquer et al, 2011;DelBove et al, 2019) and the controversial association between cholesterol levels and AD (Wood et al, 2014), which we believe may be rooted in the fact that defects in neuronal transmission could be caused by alterations in the distribution of subcellular cholesterol (DelBove et al, 2019) rather than in overall changes in cellular cholesterol concentration.…”
mentioning
confidence: 77%
“…ª 2020 The Authors The EMBO Journal 39: e103791 | 2020 point of view, the failure to cleave C99 (Shen & Kelleher, 2007;Fig 6, lower panel) would result in a futile cycle of continuous uptake of cholesterol and its mobilization from the PM to the ER, resulting in the upregulation of MAM formation and activation, which in turn would cause the upregulation of SMases, ACAT1 activity, and lipid droplet deposition. Closing the cycle, this accumulation of cholesterol in the PM would also induce APP internalization and its interaction with, and cleavage by, BACE1 (Cossec et al, 2010;DelBove et al, 2019), and the downregulation of a-secretase activity (Wang et al, 2014). Interestingly, increases in exogenous cholesterol can mimic this scenario, resulting in APP internalization and elevations in C99 (Marquer et al, 2011), increases in the Ab 42:40 ratio (Marquer et al, 2014), Tau phosphorylation (van der Kant et al, 2019), and hippocampal atrophy and cognitive impairment (Djelti et al, 2015).…”
mentioning
confidence: 99%
“…However, recent developments in high-speed high-resolution microscopy platforms have enabled sufficient spatiotemporal resolution to begin to demonstrate how endosomal APP trafficking regulates Aβ generation in living cells. In neurons, it has been shown that APP is trafficked and cleaved in pre-synaptic vesicles [25][26][27] . Using TIRF microscopy, Bauereiss et al demonstrated that APP and BACE are exocytosed to the cell surface by distinct endosomal vesicles prior to the non-amyloidogenic cleavage 28 .…”
Section: Introductionmentioning
confidence: 99%